The place of theory in Australian constitutional law: a review of T Blackshield and G Williams, Australian constitutional lawand theory, 2nd edition, Federation Press, 1998 - C. Arnott (Law Text Culture, 1998)
The success of Blackshield and Williams' Australian Constitutional Law and Theory Commentary and Materials is well indicated by the speedy appearance of its second, edition. It has rapidly and deservedly become the leading available casebook for teachers and students of law interested in the theoretical dimension to the subject. Australian constitutional jurisprudence, for those of us schooled in it, has been notorious for ignoring the political and sodal nature ofconstitutional law. By this I do not just mean the political context of legislative or government actions and constitutional challenge, but I mean the political and philosophical principles inherent in explaining, interpreting and developing the meaning of Australia's constitution. For those interested in teaching and crafting a principled constitutionalism in this latter sense, the introduction of a theoretical dimension by Blackshield and Williams has been promising.